Local spectroscopy of the Kondo lattice YbAl3: Seeing beyond the surface with scanning tunneling microscopy and spectroscopy - Wahl, Peter; Diekhöner, Lars; Schneider, M. Alexander; Treubel, F.; Lin, C.T.; Kern, Klaus (Physical Review B, 2011)
We report on an atomic-scale study of the Kondo lattice compound YbAl3 using scanning tunneling microscopy (STM) and spectroscopy (STS). An analysis of the surface orientation and structure is performed based on STM images containing more than one crystal facet. We compare tunneling spectra acquired on different facets and discuss their relation with the temperature scales observed in measurements of bulk quantities and the states observed in photoemission spectra. On specific facets, we observe strong additional resonances close to the Fermi energy which are not consistent with the characteristic energy scales found in bulk measurements, and which we interpret in terms of a modified Kondo state of the near-surface Ytterbium atoms.